The ectodomains of the lymphocyte scavenger receptors CD5 and CD6 interact with tegumental antigens from Echinococcus granulosus sensu lato and protect mice against secondary cystic echinococcosis. - Gustavo Mourglia-Ettlin; Sebastián Miles; María Velasco-; Noelia Armiger-Borràs; Marcela Cucher; Sylvia Dematteis; Francisco Lozano (Public Library of Science (PLoS), 2018)
Background Scavenger Receptors (SRs) from the host's innate immune system are known to bind multiple ligands to promote the removal of non-self or altered-self targets. CD5 and CD6 are two highly homologous class I SRs mainly expressed on all T cells and the B1a cell subset, and involved in the fine tuning of activation and differentiation signals delivered by the antigen-specific receptors (TCR and BCR, respectively), to which they physically associate. Additionally, CD5 and CD6 have been shown to interact with and sense the presence of conserved pathogen-associated structures from bacteria, fungi and/or viruses. Methodology/principal findings We report herein the interaction of CD5 and CD6 lymphocyte surface receptors with Echinococcus granulosus sensu lato (s.l.). Binding studies show that both soluble and membrane-bound forms of CD5 and CD6 bind to intact viable protoscoleces from E. granulosus s.l. through recognition of metaperiodate-resistant tegumental components. Proteomic analyses allowed identification of thioredoxin peroxidase for CD5, and peptidyl-prolyl cis-trans isomerase (cyclophilin) and endophilin B1 (antigen P-29) for CD6, as their potential interactors. Further in vitro assays demonstrate that membrane-bound or soluble CD5 and CD6 forms differentially modulate the pro- and anti-inflammatory cytokine release induced following peritoneal cells exposure to E. granulosus s.l. tegumental components. Importantly, prophylactic infusion of soluble CD5 or CD6 significantly ameliorated the infection outcome in the mouse model of secondary cystic echinococcosis. Conclusions/significance Taken together, the results expand the pathogen binding properties of CD5 and CD6 and provide novel evidence for their therapeutic potential in human cystic echinococcosis.